Land Use and Food Security in 2050 a Narrow Road - Le Mouël , Chantal; De Lattre-Gasquet , Marie; Mora , Olivier (éditions Quae, 2018)
"After a first foresight study on 'World food security in 2050' (Agrimonde), CIRAD and INRA have turned their attention to a new foresight exercise on 'Land use and food security in 2050' (Agrimonde-Terra). This new study seeks to highlight levers that could modify ongoing land-use patterns for improved food and nutrition security. Agrimonde-Terra proposes a trend analysis on the global context, climate change, food diets, urban-rural linkages, farm structures, cropping and livestock systems, and explores five scenarios. Three scenarios entitled 'Metropolization', 'Regionalization' and 'Households' are based on current competing trends identified in most world regions. Two scenarios entitled 'Healthy' and 'Communities' involve potential breaks that could change the entire land use and food security system. The 'Healthy' scenario is the only one that makes it possible to achieve sustainable world food and nutrition security in 2050. Nevertheless, current trends in agricultural and food systems in most parts of the world converge towards the 'Metropolization' scenario, which is not sustainable in terms of both land use and human health. Therefore, changing the course of ongoing trends in favor of sustainable land uses and healthy food systems will be one of the main challenges of the next decades. It will require systemic transformation, strong and coherent public policies across sectors and scales, and consistent actions from a wide range of actors. This foresight provides a large information base on land uses, food systems and food security and constitutes a tool box to stimulate debates, imagine new policies and innovations. It aims to empower decision makers, stakeholders, non-governmental organizations and researchers to develop a constructive dialogue on the futures of land uses and food security at either world, regional and national levels."